Tenophages: a novel macrophage-like tendon cell population expressing CX3CL1 and CX3CR1 - Christine Lehner; Gabriel Spitzer; Renate Gehwolf; Andrea Wagner; Nadja Weissenbacher; Christian Deininger; Katja Emmanuel; Florian Wichlas; Herbert Tempfer; Andreas Traweger (The Company of Biologists, 2019)
Tendon disorders frequently occur and recent evidence has clearly implicated the presence of immune cells and inflammatory events during early tendinopathy. However, the origin and properties of these cells remain poorly defined. Therefore, the aim of this study was to determine the presence of cells in healthy rodent and human tendon tissue fulfilling macrophage-like functions. Using various transgenic reporter mouse models, we demonstrate the presence of tendon-resident cells in the dense matrix of the tendon core expressing the fractalkine (Fkn) receptor CX3CR1 and its cognate ligand CX3CL1/Fkn. Pro-inflammatory stimulation of 3D tendon-like constructs in vitro resulted in a significant increase in the expression of IL-1β, IL-6, Mmp3, Mmp9, CX3CL1 and epiregulin, which has been reported to contribute to inflammation, wound healing and tissue repair. Furthermore, we demonstrate that inhibition of the Fkn receptor blocked tendon cell migration in vitro, and show the presence of CX3CL1/CX3CR1/EREG-expressing cells in healthy human tendons. Taken together, we demonstrate the presence of CX3CL1+/CX3CR1+ 'tenophages' within the healthy tendon proper, which potentially fulfill surveillance functions in tendons. This article has an associated First Person interview with the first author of the paper.